Upaya Pemenuhan Hak Pendidikan bagi Anak Penyandang Disabilitas di SLBN 1 Lombok Tengah - Lestari, Nadila Risti Puji; Yuliatin, Yuliatin; Hadi, M. Samsul; Sumardi, Lalu (Journal of Civic Education, 2026)
The purpose of this study is to describe efforts to fulfill the right to education for children with disabilities at SLBN 1 Central Lombok and to identify the challenges in fulfilling these rights. This study used a qualitative approach using a case study. Data collection techniques included observation, interviews, and documentation. Efforts to fulfill the right to education for children with disabilities include the implementation of an adaptive and flexible Independent Curriculum (Curriculum Merdeka), differentiated learning strategies, an emphasis on developing life skills, independence, and entrepreneurship, and providing opportunities to develop potential through academic, vocational, and personal development activities. Furthermore, the school provides facilities, learning equipment and aids, and supportive classroom environments, yet challenges remain, including a limited number of qualified educators for various types of disabilities, the diversity of student disabilities, and limitations in educational facilities and services, such as the lack of a LAS skills room and ongoing classroom renovations. Therefore, support from various parties is needed so that inclusive education at SLBN 1 Central Lombok runs optimally and sustainably.